PENINGKATAN KEMAMPUAN DAN KETERAMPILAN SISWA DI SMP METHODIST BERASTAGI MELALUI KURSUS GRATIS - Kammer Tuahman Sipayung; Santri Subroto Simanjuntak; Herlina Turnip; Eni Julita Br Munthe; Ita Mariani Br Manurung; Jeri Alfandi Ginting (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2022)
Students’ ability and skill are indicators of education result through long process of teaching and learning. Since the out-break of pandemic Covid-19, some schools have certain problems on delivering their materials or knowledge to the students. The aims of this activity to help students to improve their ability on math  and language  skill on English and Indonesian through free course for a month. To achive the goals above, extracuriculer lecturing and tutoring were done. This activities were started from preparation also coordination to the principle of junior high school at Metodist on Berastagi. The result of this activity shown that there was an improvement on math ability and language skill in term of English and Indonesia. This activity helped students on junior high school to improve their weakness on Math, English and Indonesian.